Allies at odds : the Andean church and its indigenous agents, 1583-1671 - Charles, John (University of New Mexico Press, 2010)
Focusing on the highland parishes of the Lima archdiocese, John Charles explores the vital, often conflictive role indigenous agents played in the creation of Andean Christian society. Torn between their obligation to enforce colonial laws and their customary obligation to protect native communities from the colonizers’ abuses, indios ladinos used the Spanish language to complicate the Church’s efforts to evangelize on its own terms. Utilizing a vast body of literary activity, Allies at Odds provides perspective on the Spanish cultural values that shaped the literary activity of native Andeans and that native Andeans had a part in shaping.